2022
DOI: 10.3390/brainsci12091258
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Long-Term Effects: Is There an Impact on the Simple Reaction Time and Alternative-Forced Choice on Recovered Patients?

Abstract: A comparative single-evaluation cross-sectional study was performed to evaluate cognitive damage in post-COVID-19 patients. The psychophysics tests of Two-Alternative Forced Choice (2AFC) and Simple Reaction Time (SRT), under a designed virtual environment, were used to evaluate the cognitive processes of decision-making, visual attention, and information processing speed. The population under study consisted of 147 individuals, 38 controls, and 109 post-COVID patients. During the 2AFC test, an Emotiv EPOC+® h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Likewise, in a study contrasting 109 post-COVID-19 patients against on 38 controls, those recovering from severe COVID-19 reportedly had poorer performance in tasks requiring high visual sensitivity and were affected by slower processing information speed, as a possible damage to visual or nervous system. By contrast, work performance of patients with mild/moderate COVID-19 was similar to never infected subjects in the latter study [ 9 ].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Likewise, in a study contrasting 109 post-COVID-19 patients against on 38 controls, those recovering from severe COVID-19 reportedly had poorer performance in tasks requiring high visual sensitivity and were affected by slower processing information speed, as a possible damage to visual or nervous system. By contrast, work performance of patients with mild/moderate COVID-19 was similar to never infected subjects in the latter study [ 9 ].…”
Section: Discussionmentioning
confidence: 84%
“…Reduced work ability and quality of life have also been reported in relation to persisting COVID-19 symptoms. [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the neuropsychological profile indicates impairment in the executive domain, tests grouped under executive functions can also be considered to involve processing speed. Several previous studies have related slowness with illness severity [ 5 , 11 , 15 ]. Our results support this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…However, among non-ICU patients, the cognitive composite score did not differ between those who were hospitalized and those who were not [ 14 ]. In a similar study performed with a healthy control (HC) group, patients with severe PCC showed lower processing speed than those with mild-moderate PCC and healthy control participants [ 15 ]. In a Finnish study, both ICU and hospitalized patients underperformed patients treated at home in the total cognitive score at 6 months post-COVID.…”
Section: Introductionmentioning
confidence: 99%
“…The seven studies which have investigated the long-term effects of COVID infection (9 to 12 months) found a deterioration of cognitive performance in different cognitive domains, such as in overall cognition [ 91 ], memory [ 90 , 92 , 93 , 94 ], attention [ 95 , 96 ], executive functions [ 90 , 92 ] and visuospatial abilities [ 90 ].…”
Section: Resultsmentioning
confidence: 99%